Clinical Outcomes Of Diode Laser–Assisted Endoscopic Resection Of Superficial Neoplasms Of The Upper Gastrointestinal Tract - Yigitaliev Sardor Khusanboevich; Mardonov Jamshid Normurotovich; Yigitalieva Nasima Numovna; Umrzakova Iroda Ilkhomjon qizi (International Journal of Medical Sciences And Clinical Research, 2025)
Superficial lesions of the upper gastrointestinal tract are frequently detected during routine endoscopy. Despite the availability of different endoscopic techniques, incomplete resection, bleeding and local recurrence remain important clinical problems. Aim: To assess the safety and clinical effectiveness of a diode laser–assisted endoscopic resection technique combined with submucosal gel injection in patients with superficial neoplasms of the upper gastrointestinal tract. Materials and Methods: A total of 252 patients with superficial upper gastrointestinal lesions were included in this comparative study. The control group consisted of 134 patients treated with conventional endoscopic techniques. The main group included 118 patients who underwent a novel procedure based on submucosal injection of a Hemoben–based gel followed by diode laser excision. The main outcomes were en bloc resection rate, intraoperative and delayed bleeding, perforation, postoperative complications (according to the Clavien–Dindo classification), hospital stay, and recurrence rate during a follow-up period of 6–18 months. Results: En bloc removal was achieved more often in the main group (82.6%) than in the control group (69.8%). Clinically significant bleeding during the procedure was observed only in the control group (6.6%), while it was not recorded in the main group. Delayed bleeding was less frequent in the main group (0.6% vs 3.3%). The overall complication rate was significantly lower in patients treated with the new technique (0.8% vs 4.5%, p = 0.011). The recurrence rate decreased from 17.4% in the control group to 3.1% in the main group. Patients in the main group also had a shorter hospital stay (3.1 ± 0.9 days vs 3.5 ± 1.2 days, p < 0.05). Conclusion: Diode laser–assisted endoscopic resection with submucosal gel injection is a safe and effective method for treating superficial neoplasms of the upper gastrointestinal tract. The technique improves the completeness of resection and reduces the risk of bleeding, postoperative complications and local recurrence compared with standard endoscopic approaches.